(untitled) (Jurnal Ilmu Manajemen dan Bisnis, 2023)
This research aims to find out the productivity of palm sugar business actors in mongiilo village, this type of research is qualitative research with a descriptive approach that is a problem-solving procedure that is investigated by making a social reconstruction, and further systematically describes the object of research. In data collection, researchers consider the selection of the first informant to be targeted, namely the palm sugar business itself which is the main key. After doing this research, it is known that, palm sugar business actors are workers who never know the word tired in doing activities to work as palm sugar business actors, because in its implementation the palm sugar business actors do work from morning to evening to wait for their production results. The level of productivity depends on traders who buy palm sugar in the market not only that the role of middlemen in the midst of palm sugar business actors determines the results of production for the perpetrators